FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KAPASITAS VITAL PARU PADA PEKERJA INDUSTRI PENGOLAHAN KAYU DI PT. X JEPARA - Agita Oviera; Siswi Jayanti; Suroto Suroto (Jurnal Kesehatan Masyarakat (Undip), 2016)
Manufacturing industry could potentially cause wood dust contamination in the workplace. The result of the pre-survey on April 2015, there were 8 out of 10 workers experiencing health problems in form of coughing and breathing complication. The purpose of this study was to determine the factors associated with lungs vital capacity on workers of wood processing industry in PT. X Jepara. The method used explanatory research using quantitative approach with cross sectional study design. The dependent variable were lungs vital capacity and measurement using spirometry measurements, the independent variable were age, gender, nutritional status, history of lung disease, smoking habits, exercise habits, and the use of masks. Population and sample were all the production process workers of PT. X, Jepara with a total number of 37 workers. Data were analyzed using univariate and bivariate analysis with chi-square contigency test (significance level 0,05). The results of lungs vital capacity measurement were 8 (21,6%) workers had  abnormal vital lung capacity and 29 workers had normal vital lung capacity. Results of bivariate analysis showed that there is an association between gender with lung vital capacity (p-value 0,007) and smoking habits with lung vital capacity (p-value 0,000). As for the other five variables, there were no association with lung vital capacity found, which were age (p-value 0,199), nutritional status (p-value 0,497), history of lung disease (p-value 0,974), exercise habits (p-value 0,451), and use of masks (p-value 0,097). It is concluded from the study that there is an association between gender and smoking habit with vital lung capacity.